A Cross-Sectional Study of Elderly Patients with Electrolyte Imbalance and its Relation with the Outcomes like Complications and Hospital Stay during Orthopedic Surgery - Ashima Badyal; Pallavi Mahajan; Manish Singh; Sanjeev Gupta (JK Science, 2025)
Background: Post-operative electrolyte imbalance (EI) has been found to be a marker of poor medical status and a risk factor among elderly orthopedic patients. Aims: To investigate the incidence and severity of imbalances of sodium/ potassium/ calcium/ magnesium and phosphate, and also to study its association with the outcome and duration of stay in hospital. Material and Methods: It was a prospective cross-sectional study conducted in Department of Orthopedics and Department of Biochemistry, GMC Jammu, from January-2022 to June-2022 on 60 elderly patients, admitted in Emergency Orthopedic Wards, to determine the incidence of EI. Results: 32 (53.33%) of patients were females, 6 (10%) were >80 years, median age was 69 ± 6.4 years. Common presentations: disorientation or confusion 20 (33.33%); nausea or vomiting 16 (26.67%). High prevalence of hyponatremia 10 (16.67%) and hypokalemia 6 (10%) was seen. The mean length of hospital stay for patients with hyponatremia/hypernatremia was 9.5 days and 5.75 days respectively, and for hypokalemia/hyperkalemia: 9.5 days and 8.2 days respectively. The mean hospital stay of the patients with EI was 6.5 ± 1.3 days, with 8 (13.33%) readmissions within 30 days from discharge. Conclusion: EI was found to prolong length of stay and affect readmission, as well as mortality among elderly patients undergoing orthopedic surgeries.